Pengaruh Ukuran Perusahaan, Reputasi Underwriter, dan Persentase Penawaran Saham Terhadap Underpricing Saham Sebagai Pengambilan Keputusan Melakukan IPO di BEI - Nilam Larasati; Miladiah Kusumaningarti; Agus Athori (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of firm size, underwriter reputation, and stock offering percentage partially and simultaneously on underpricing as a company’s decision making to conduct an IPO on IDX. This study is an associative research with quantitative data. The population of this study is all companies that have conducted an IPO on the Indonesia Stock Exchange (IDX) in 2017 to 2021, totaling 253 companies. Sampling was carried out using a purposive sampling method which resulted in 36 companies. The technique used is multiple linear regression. The results of the study partially show that firm size with a coefficient value 0,002 and a sig. 0,973 has a positive and insignificant effect on underpricing. Meanwhile, underwriter reputation with a coefficient value -0,018 and a sig. 0,796, as well as stock offering percentage with a coefficient value -0,145 and a sig. 0,696 has a negative and insignificant effect on underpricing. Simultaneously, the result of the study produce sig. 0976, which shows there is insignificant influence between firm size, underwriter reputation, and stock offering percentage on underpricing at IPO companies on the IDX in 2017 to 2021